Diseño de experiencia de los espectadores de una coreografía a partir de variables que impactan el nivel de interés del público (2020)
Purpose - The purpose of this investigation was the intervention of the loss of connection of the spectators with scenic works in particular with dance works. This is because current performing arts companies tend to ignore the importance of those factors that maximize attention and that in the same way direct the emotions of their viewers. Based on this, different experiments were carried out in which four variables that directly affect the creation of a choreography and that have a direct relationship with the excitement of the public observing a dance work were evaluated. This was very useful to obtain important results that allowed the construction of an effective solution. Design/methodology/approach - To face this problem, various experiments were carried out. The patterns that exist at the time of expressing different emotions with 18 participants were studied and how dancers usually express them from different dance styles. The emotional responses that various dance stagings cause in the audience were also studied, using the space of Arousal and Valencia. Finally, various dance techniques and their mechanisms for projecting and stimulating the spectator's excitement were analyzed. During the investigation, a corpus of 10 dance pieces was created, noting the essential structural variables that impact the level of public interest: number of scenes, duration, number of dancers per scene, location of dancers on stage, pulses per minute (BPM) of music per scene.